Pengaruh Variasi Waktu Kontak dan Dosis Adsorben Fly ash teraktivasi NaOH terhadap Adsorpsi Metilen Biru - Brilian Gema Morentera; Sri Wahyuningsih; Dyan Hatining Ayu Sudarni (Eksergi, 2022)
A rapid growth of  textile industry creates a new problems  on environment, one of those is the presence of dye waste. Methylene blue is one of the dyes which is toxic to living things, one of those triggers cyanosis for human and bother photosyntesis  of algae. Therefore, it needs the effort to reduce, one of those is by adsorption. This study aims to determined the effect of dosage adsorbent variation and contact time variation to adsorb methylene blue. Adsorption is an adsorbate molecule absorption process that occurs on the surface of the adsorbent. This study used fly ash from PG. Pagottan and has been activated by NaOH. Measure method of this study using UV-Vis Spectrophotometry to measure concentration of methylene blue at maximum wavelenght. Based on data, NaOH-activated fly ash and non-activated fly ash  following Langmuir isotherm adsorption, it mean a monolayer site is formed. Adsorption capacity also increase after activation, it about 21,74 mg/g to 23, 25 mg/g. Based on the study fly ash has a potential as a new adsorbent.